2019
DOI: 10.1016/j.jbankfin.2019.105662
|View full text |Cite
|
Sign up to set email alerts
|

The effect of experts’ and laypeople’s forecasts on others’ stock market forecasts

Abstract: With a large-scale online experiment with 1593 participants from the U.S. and the U.K. we explore whether and how people working in the finance industry and laypeople from the general population are influenced by information on other people's forecasts when making forecasts on the future development of two indices and two stocks. We find that (i) laypeople's forecasts are strongly influenced by information they get on other subjects' forecasts, while financial professionals are much less influenced by informat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The study further depicted that predictability can be improved by delicately balancing relevant information and noise through moderate filters based on how accurate the forecasts of the past performance have been. Huber, Huber, and Hueber (2019) examined if and how, finance professionals and laypeople from the general population get influenced by receiving additional information on other people's forecasts while making predictions on the future of two stocks and two indices. The findings of the study indicated that the predictions made by laypeople are strongly influenced by information on other people's forecasts whereas finance professionals are not very sensitive to any such information signals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study further depicted that predictability can be improved by delicately balancing relevant information and noise through moderate filters based on how accurate the forecasts of the past performance have been. Huber, Huber, and Hueber (2019) examined if and how, finance professionals and laypeople from the general population get influenced by receiving additional information on other people's forecasts while making predictions on the future of two stocks and two indices. The findings of the study indicated that the predictions made by laypeople are strongly influenced by information on other people's forecasts whereas finance professionals are not very sensitive to any such information signals.…”
Section: Literature Reviewmentioning
confidence: 99%